(untitled) (Global Journal of Science Frontier Research, 2021)
Automobiles are associated with a number of externalities like energy-and emissionintensity, congestion, and road fatalities. These could be reduced by controlling the four components: carbon intensity of fuels, energy intensity of mobility (technology oriented); and modal structure of mobility and the volume of mobility (behavior oriented also called Travel Demand Management). While most studies focus on the technological aspects of mitigation and tend to ignore the behavioural aspects of mobility, this paper is an attempt to highlight the need and importance of behavioural approaches in solving transport problems. In order to practically understand the dynamics of it, it takes up a study of transport sector in Himachal Pradesh and examines the external effects in the presence of information asymmetries. The study finds that the current transport policy in Himachal Pradesh fails to provide transport infrastructure of high standards, promote non-discriminatory competition within and between modes, and ensure tackling externalities. It therefore makes a case for adopting behavioural initiatives to reduce the travel demand.